Realizing the Full Potential of Clinical Decision Support: Translating Usability Testing into Routine Practice in Health Care Operations - Kandaswamy, Swaminathan; Williams, Herbert; Thompson, Sarah Anne; Dawson, Thomas Elijah; Muthu, Naveen; Orenstein, Evan William (Applied Clinical Informatics, 2024)
Background Clinical Decision Support (CDS) tools have a mixed record of effectiveness, often due to inadequate alignment with clinical workflows and poor usability. While there is a consensus that usability testing methods address these issues, in practice, usability testing is generally only used for selected projects (such as funded research studies). There is a critical need for CDS operations to apply usability testing to all CDS implementations.Objectives In this State of the Art/Best Practice paper, we share challenges with scaling usability in health care operations and alternative methods and CDS governance structures to enable usability testing as a routine practice.Methods We coalesce our experience and results of applying guerilla in situ usability testing to over 20 projects in a 1-year period with the proposed solution.Results We demonstrate the feasibility of adopting “guerilla in situ usability testing” in operations and their effectiveness in incorporating user feedback and improving design.Conclusion Although some methodological rigor was relaxed to accommodate operational speed, the benefits outweighed the limitations. Broader adoption of usability testing may transform CDS implementation and improve health outcomes.
Keywords: clinical decision support; usability testing; translating research